Rotavirus vaccine-derived cases in Belgium: Evidence for reversion of attenuating mutations and alternative causes of gastroenteritis. Issue 35 (19th August 2022) - Simsek, Ceren; Bloemen, Mandy; Jansen, Daan; Descheemaeker, Patrick; Reynders, Marijke; Van Ranst, Marc; Matthijnssens, Jelle
Highlights: Rotavirus vaccine-derived AGE cases were detected in Belgium in the post-vaccine era. There was limited evidence for vaccine strain circulation with scarce point mutations in both shed and circulating strains. 90% of the mutations were non-synonymous and several amino acid substitutions were shared among patients. Some substitutions could be revertants towards the unattenuated vaccine precursor strain, albeit with low safety concerns. In 35% of the cases, the AGE was estimated to be of non-rotavirus etiology. Abstract: Since the introduction of live-attenuated rotavirus vaccines in Belgium in 2006, surveillance has routinely detected rotavirus vaccine-derived strains. However, their genomic landscape and potential role in gastroenteritis have not been thoroughly investigated. We compared VP7 and VP4 nucleotide sequences obtained from rotavirus surveillance with the Rotarix vaccine sequence. As a result, we identified 80 vaccine-derived strains in 5125 rotavirus-positive infants with gastroenteritis from 2007 to 2018. Using both viral metagenomics and reverse transcription qPCR, we evaluated the vaccine strains and screened for co-infecting enteropathogens. Among the 45 patients with known vaccination status, 39 were vaccinated and 87% received the vaccine less than a month before the gastroenteritis episode. Reconstruction of 30 near complete vaccine-derived genomes revealed 0–11 mutations per genome, with 88% of them being non-synonymous. This, in combination with several shared amino acid changes among strains, pointed at selection of minor variant(s) present in the vaccine. We also found that some of these substitutions were true revertants (e.g., F167L on VP4, and I45T on NSP4). Finally, co-infections with known (e.g., Clostridioides difficile and norovirus) and divergent or emerging (e.g., human parechovirus A1, salivirus A2) pathogens were detected, and we estimated that 35% of the infants likely had gastroenteritis due to a 'non-rotavirus' cause. Conversely, we could not rule out the vaccine-derived gastroenteritis in over half of the cases. Continued studies inspecting reversion to pathogenicity should monitor the long-time safety of live-attenuated rotavirus vaccines. All in all, the complementary approach with NGS and qPCR provided a better understanding of rotavirus vaccine strain evolution in the Belgian population and epidemiology of co-infecting enteropathogens in suspected rotavirus vaccine-derived gastroenteritis cases.